Generalized livedo reticularis like eruption induced Generalized livedo reticularis like eruption induced by trimethoprim/sulfamethoxazole: A case report with by trimethoprim/sulfamethoxazole: A case report with concomitant myelosuppression - Pinar Incel Uysal; Basak Yalcin; Onder Bozdogan (Our Dermatology Online, 2017)
Livedo reticularis is a reticular discoloration of the skin because of the vascular anatomy of the skin. The condition most commonly affects the legs. Drug induced livedo reticularis which is an acknowledged side effect of amantadine, tends to be widespread, asymptomatic, benign rash. There are also reports of livedoid eruption induced with drugs including dapsone, imatinibe, gefitinibe. We describe a case of livedo reticularis like eruption and haemotological toxicity with trimetophrim-sulfamethoxazole. The purpose of this report is to remind clinicians of this rare, benign side effect of the common prescribed medication.